2011
DOI: 10.1262/jrd.10-029a
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dihydroxyflavone Acts as an Antioxidant and Antiapoptotic Agent to Support Bovine Embryo Development In Vitro

Abstract: Abstract. The effects of two antioxidants, superoxide dismutase (SOD) and the flavonoid 3,4-dihydroxyflavone (DHF), on bovine embryo development in vitro were examined. Blastocyst development, total cell and inner cell mass (ICM) numbers, intracellular levels of reactive oxygen species (ROS), apoptotic indices and gene expression levels were examined before and after treatment of day 2 bovine embryos (≥2-4 cells) with various concentrations of 3,4-DHF or SOD for 6 days. Statistical analysis was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
(25 reference statements)
1
17
0
Order By: Relevance
“…Generally, it is considered that stimulated levels of the enzyme have evolved to address increased free-radical production during inflammatory episodes. The high MnSOD expression levels found in our results were consistent with those in previous reports that suggested that increased levels of MnSOD might be related to inadequate reprogramming of the donor genome in NT embryos [34][35][36]. However, the high expression levels of MnSOD in Group 3 might have been due to these embryos' increased vitality.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, it is considered that stimulated levels of the enzyme have evolved to address increased free-radical production during inflammatory episodes. The high MnSOD expression levels found in our results were consistent with those in previous reports that suggested that increased levels of MnSOD might be related to inadequate reprogramming of the donor genome in NT embryos [34][35][36]. However, the high expression levels of MnSOD in Group 3 might have been due to these embryos' increased vitality.…”
Section: Discussionsupporting
confidence: 91%
“…Also supplementation of polyphenols promotes development of pig [122] and mouse [123] embryos as well as cow embryos [121,124]. Addition of flavonoids also affected the expressions of Mn-SOD, survivin, Bax-I, Glut-5 and IFN-τ genes in cow embryos as well as improving development [121].…”
Section: Development Of Embryosmentioning
confidence: 97%
“…They are characterized by the presence of several groups involved in phenolic structures and include the flavonoids and phenolic acids. Flavonoids promoted development of bovine embryos culture both in high (20%) and low (5%) O 2 tension with reducing the intracellular ROS [121]. Also supplementation of polyphenols promotes development of pig [122] and mouse [123] embryos as well as cow embryos [121,124].…”
Section: Development Of Embryosmentioning
confidence: 99%
“…It inhibits glutamate-triggered apoptosis induced by glutathione (GSH) depletion and ROS production and has antioxidant activity in neurons by acting as a selective tyrosine kinase receptor B agonist [27, 28]. In addition, 3,4-dihydroxyflavone (3,4-DHF) supports bovine embryo development in vitro as an antioxidant and anti-apoptotic agent [29], and 7,8-DHF appeared to have protective effect against oxidative stress [30]. However, the effects of 7,8-DHF for porcine oocytes and embryos have not been well investigated.…”
mentioning
confidence: 99%